The influence of nitric oxide delivery on the processes of apoptosis, necroptosis and pyroptosis in the renal parenchyma after simulating cardiopulmonary bypass: an experimental study - M. A. Tyo; N. O. Kamenshchikov; Yu. K. Podoksenov; A. V. Mukhomedzyanov; L. N. Maslov; I. V. Kravchenko; E. A. Churilina; B. N. Kozlov (Вестник анестезиологии и реаниматологии, 2024)
The objective was to study the effect of the delivery of exogenous nitric oxide on the severity of apoptosis, pyroptosis, and necroptosis of the renal parenchyma after simulating cardiopulmonary bypass and cardiopulmonary bypass with circulatory arrest.Materials and Methods. 24 Altai breed rams were randomized into 4 equal groups. In the CPB and CPB+NO groups, we simulated cardiopulmonary bypass without circulatory arrest. In the CPB+CA and CPB+CA+NO groups, we simulated cardiopulmonary bypass with circulatory arrest. In the CPB+NO, CPB+CA+NO groups, NO was given perioperative in concentration of 80 ppm. In the CPB, CPB+CA groups, we supplied a standard oxygen-air mixture without NO.Results. In the CPB+CA+NO group, the TNF-α concentration was statistically significantly lower: 899 [739; 1019] ng/g compared to the CPB+CA group 1716 [1284; 2201] ng/g, p = 0.026. The remaining markers of programmed cell death did not differ between groups.Conclusions. Perioperative nitric oxide delivery reduces the expression of the extrinsic pathway of apoptosis of renal parenchyma cells in simulating operations with artificial circulation and circulatory arrest. Perioperative nitric oxide delivery at a dose of 80 ppm does not increase the processes of apoptosis, pyroptosis, and necroptosis in renal parenchyma.